Active viral genes in transformed cells lie close to the nuclear cage. - Cook, P; Lang, J; Hayday, A; Lania, L; Fried, M; Chiswell, D; Wyke, J (1982)
Nuclear DNA is looped by attachment to a matrix or cage. Using nine different lines transformed by polyoma or avian sarcoma virus, we have mapped viral sequences integrated within these loops. In all lines that contain high concentrations of viral transcripts and express the transformed phenotype, the integrated viral genes lie close to the points of attachment to the cage. Integration of polyoma DNA induces outlying cellular sequences to become closely associated with the cage. The strength of this correlation between gene activity and proximity to the cage was examined using sub-clones of one avian sarcoma virus transformant. Proviral sequences are closely associated with the cage in this transformant, much less so in two untransformed 'flat revertants' which contain no detectable viral transcripts but regain their close association with the cage in two retransformed derivatives.